2017
DOI: 10.1111/jocn.13699
|View full text |Cite
|
Sign up to set email alerts
|

Complexities of emergency communication: clinicians’ perceptions of communication challenges in a trilingual emergency department

Abstract: The findings of this study may shed light on the unique conditions faced by clinicians, particularly in relation to communication, in the complex trilingual healthcare context of an emergency department similar to those in Hong Kong, and provide potential policy solutions for barriers to improve communication in such settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 39 publications
(73 reference statements)
4
23
0
1
Order By: Relevance
“…We found that the CNs and the DOCs play a vital role in maintaining information flow within their own and across other professions in the ED, and this finding is congruent with the results of a previous study that reviewed effective communication in CL [16]. Similar to the study findings, Pun et al [36, 37] found that information was repeated several times. We found some differences between CL activities performed by CNs and DOCs.…”
Section: Discussionsupporting
confidence: 91%
“…We found that the CNs and the DOCs play a vital role in maintaining information flow within their own and across other professions in the ED, and this finding is congruent with the results of a previous study that reviewed effective communication in CL [16]. Similar to the study findings, Pun et al [36, 37] found that information was repeated several times. We found some differences between CL activities performed by CNs and DOCs.…”
Section: Discussionsupporting
confidence: 91%
“…Medication communication has been assessed ethnographically from the interplay viewpoint between nurses, patients, physicians and students (Liu, Gerdtz, & Manias, 2015, 2016;Rutledge, Retrosi, & Ostrowski, 2018;Schoenthaler, Allegrante, Chaplin, & Ogedegbe, 2012;Tobiano et al, 2019), but also concerning professionals’ tendency to follow communicated guidelines (Karttunen et al, 2020). Studies of medication communication have been conducted on emergency situations concerning language barriers (Pun, Chan, Murray, Slade, & Matthiessen, 2016), racial issues affecting medication communication (Schoenthaler et al, 2012) and environmental issues of communication (Liu et al, 2014;Manias, Cranswick, et al, 2019;Yu et al, 2018). Nevertheless, the relative frequency of a wide variety of specific communication issues has not been measured using incident reports submitted in acute care.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research shows that health communication—between patients and clinicians, as well as between clinicians—is vital to quality health care (Pun, Chan, Matthiessen, Slade, & Murray, ; Slade et al, ). When health communication is unclear or inaccurate, patient safety is significantly compromised.…”
Section: Introductionmentioning
confidence: 99%